Internet of things-based robot to take care of the Coronavirus patients and sterilize quarantine rooms - Huthaifa Ahmad Al-Issa; Issam Trrad (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The medical staff is the first part which is affected in the COVID-19 pandemic, then the workers, whether in the hospital or quarantine hotels who are responsible for cleanliness and sterilization. The goal is to reduce the number of injured and preserve human safety. This led us to think deeply to solve this problem and make the life healthier and to reduce the spread of the virus by using internet of things (IoT). The goal of the research is to develop a special robot to sterilize quarantine rooms and hospitals, measure the patient’s temperature and heart rate, in addition to transporting medicines to patients in order to preserve the safety of the medical staff. So, in order to accomplish this purpose, we will create a proof of concept for the robot. Our robot will have a system capable of performing pre-programmed acts, either under direct human control or under the control of computer programs. This paper can be the basic for future research in the same field.